Moduli stabilisation for chiral global models - Cicoli, Michele; Mayrhofer, Christoph; Valandro, Roberto (Journal of high energy physics, 2012)
We combine moduli stabilisation and (chiral) model building in a fully con-sistent global set-up in Type IIB/F-theory. We consider compactifications on Calabi-Yau orientifolds which admit an explicit description in terms of toric geometry. We build globally consistent compactifications with tadpole and Freed-Witten anomaly cancellation by choosing appropriate brane set-ups and world-volume fluxes which also give rise to SU(5) or MSSM-like chiral models. We fix all the Kähler moduli within the Kähler cone and the regime of validity of the 4D effective field theory. This is achieved in a way compatible with the local presence of chirality. The hidden sector generating the non-perturbative effects is placed on a del Pezzo divisor that does not have any chiral intersection with any other brane. In general, the vanishing D-term condition implies the shrinking of the rigid divisor supporting the visible sector. However, we avoid this problem by generating r < n D-term conditions on a set of n intersecting divisors. The remaining (n − r) flat directions are fixed by perturbative corrections to the Kähler potential. We illustrate our general claims in an explicit example. We consider a K3-fibred Calabi-Yau with four Kähler moduli, that is a hypersurface in a toric ambient space and admits a ‘simple’ F-theory up-lift. We present explicit choices of brane set-ups and fluxes which lead to three different phenomenological scenarios: the first with GUT-scale strings and TeV-scale SUSY by fine-tuning the background fluxes; the second with an exponentially large value of the volume and TeV-scale SUSY without fine-tuning the background fluxes; and the third with a very anisotropic configuration that leads to TeV-scale strings and two micron-sized extra dimensions. The K3 fibration structure of the Calabi-Yau three-fold is also particularly suitable for cosmological purposes.